"Molluscum" conditions in dermatology - Vishal Gaurav; Chander Grover (Wolters Kluwer Medknow Publications, 2021)
In dermatology, the word "molluscum" is used as a prefix for infective and non-infective conditions. The term is used to describe soft papules or nodules with or without central umbilication, which is not a necessary qualification. This article attempts to summarise the conditions in dermatology with the epithet "molluscum" and discuss them in brief.